Nośność graniczna pręta z karbami obciążonego siłą podłużną i momentem zginającym - MIELNICZUK, Jan (Engineering Transactions, 1971)
The limiting load of a rod with notches loaded with longitudinal force and bending momentThe object of this paper is the determination of the limit load of a fiat rod with angular notches submitted to simultaneous stretching by an axial force N and bending by the bending moment M.After application of the basic compounds, the existence of two types of solutions is demonstrated, in both a fiat state of strain and a fiat state of stress. The boundary curves f(m, n) = 0 obtained enable determination of the coefficients of the increase of limit load in relation to the load of a rod without notches, for the whole range of forced loads and moment loads depending on the opening angle of the notch.